Wireless Power Transfer through Inductive Coupling - Shakya, Apekshya; Prasad Devkota, Bipin; Thakur, Purshottam; Bhattarai, Manish (KEC Journal of Science and Engineering, 2026)
This paper proposes the wireless power transfer (WPT) through inductive coupling (IC). WPT can be described as the transfer of electrical energy from the source to the electrical load without using conductors connecting between transmitter and receiver coil. This paper highlights significant studies on the short-range inductive coupling and challenging in achieving high efficiency and safety over long distances.